Design of Feasible Energy Generation Using Solar Panel and Control Using an IoT - Prabha, G; Mohana sundaram, K (International Journal of Engineering and Technology, 2018)
The Internet of Things Technology enhances the control of load from solar power generation. Solar power generation is one of the fast growing and most advantageous renewable energy sources of power generation worldwide. These days there is an increase in demand of electrical energy in our daily life. Solar energy has the greatest potential in the long term and is predicted to play a major role in forthcoming years. The implementation of two modes of power supply has been done, one is the normal power supply mode and the other mode is by solar power generation in which the load can be controlled using IoT in pc or mobile phone. This will facilitate in energy conservation.Â